Effect of acetaminophen on hepatic enzymes and renal analytes of ovary-hysterectomized dogs - Olivares-Muñoz, Angelica; Martínez-Hernández, Ingrid; Medina-Magariño, Esther; Martínez-Hernández, Karen; Espín- Iturbe, Teresa; Gamboa-Prieto, Jannete; Canales-Rubio, Miguel; Bravo-Ramos, José (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Pain treatment in companion animals is of great importance nowadays. Alternative pain therapies should be studied in small species to improve life quality and well-being of patients. For years, acetaminophen has been misused in dogs and cats, producing toxic effects after administration at high doses. Objective: To evaluate the effects of pre- and post-surgical administration of acetaminophen (also called paracetamol) on renal and hepatic enzymes in dogs undergoing ovarian hysterectomy surgery, and its effect as a trans- and post-surgical analgesic therapy. Methods: An acetaminophen dose was administered 30 minutes before surgery and 48 hours after the procedure. Pain was assessed with the Glasgow Pain Scale during surgery and at 2, 6, 12 and 24 hours after the surgical procedure. Blood studies were performed seven days before surgery and five days after to evaluate the effect of acetaminophen on liver enzymes and renal analytes. Results: No significant changes in renal analytes and liver enzymes were observed after drug application every 6 and 8 hours for 48 hours. Furthermore, anesthesia and analgesia remained stable during the surgical procedure and a low score on pain scale was observed, indicating absence of postoperative pain despite the total time of surgery was longer than usual. Conclusion: Acetaminophen is an excellent analgesic for prolonged surgery and also for postoperative pain. Furthermore, it does not produce hepatic or renal alterations at the tested doses.